Redesigning nutritional supplements for older adults: a flavour chemistry and nutrition approach - Lester, Sophie (2021)
Within the increasing older population, there is a burden of undernutrition. The prescription of oral nutritional supplements (ONS) for those who are undernourished, or at risk of undernutrition, can help improve nutritional status, but the patient must consume an adequate quantity of ONS to gain the clinical benefits.